Black Banking–Problems and Prospects - Irons, Edward D. (Journal of Finance, 1971)
Edward D. Irons, Black Banking–Problems and Prospects, The Journal of Finance, Vol. 26, No. 2, Papers and Proceedings of the Twenty-Ninth Annual Meeting of the American Finance Association Detroit, Michigan December 28-30, 1970 (May, 1971), pp. 407-425